Social Dynamics: A Phenomenological Exploration of the Lived Experiences of Social Science Professionals Across Generations - FUNGO, ERIC; GRATA, AMANDO (International Journal of Contemporary Studies in Education, 2025)
This study explores the interplay between social dynamics and the career development of social science professionals, focusing on how generational identities are influenced by and contribute to these dynamics. As societies evolve, the resulting shifts in behaviors, attitudes, and beliefs significantly impact individuals' career trajectories. This qualitative research employs a descriptive phenomenological approach to explore the lived experiences of social science professionals from different generations—Baby Boomers, Generation X, Millennials, and Generation Z. By analyzing participants' narratives, the study uncovers how social environments, shaped by historical, political, and economic contexts, inform career choices and professional growth. Key themes emerged from the analysis, highlighting distinct characteristics and motivations across generations. Baby Boomers exemplified resilience and adaptability, reflecting on their diverse career paths. Generation X demonstrated a commitment to education and innovation amidst systemic challenges. Millennials articulated a strong drive for social change, while Generation Z exhibited a search for meaning in their evolving professional identities. The findings emphasize that career development is a multifaceted journey, shaped by social dynamics that extend beyond personal choice to encompass broader societal influences. This research contributes to a deeper understanding of how generational experiences impact career decision-making, offering insights into fostering an adaptable and resilient workforce capable of navigating contemporary social challenges.